Medicinal and Aromatic Plants in Agricultural Research When Considering Criteria of Multifunctionality and Sustainability (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Medicinal and aromatic plants (MAPs), as open-field crops, play an important role in multifunctional and sustainable agriculture as a result of their low energy requirements for cultivation and their many avenues of use, from the production of nutraceuticals, phytonutrients, and phytotherapy to land valorization. This Special Issue of Agriculture, “Medicinal and Aromatic Plants in Agricultural Research when Considering Multifunctionality and Sustainability Criteria”, aims to illustrate the role of MAPs in agriculture in low-impact farming practices, and the benefits they can generate in terms of functional products. This Special Issue covers all research aspects related to MAPs, including a number of scientific macro-areas, such as agronomy, chemistry and pharmacy, ethnobotany and ethnopharmacology, food and nutrition, and ecology. Key topics in this Special Issue include, but are not limited to, the following: Sustainable agricultural practices of MAPs; Breeding and germplasm preservation of MAPs; The biodiversity of MAPs; The conservation of cultivated and wild MAPs; Ethnobotany and ethnopharmacology; Phytotherapy, phytochemistry, and phytopharmacology; Essential oils and secondary metabolites; Functional foods and MAPs; MAPs and degraded and marginal land recovery; The global marketing of MAPs; The legislation of MAPs.